Implicações dos processos licitatórios na psicodinâmica do trabalho de uma unidade pública de alimentação e nutrição - Melo, Vangelina Lins (2013)
Workers of the segment are alimentation exposed to situations that can change your health for poor working conditions, problems of environment, work processes and equipment and supplies probably acquired in bidding. Considering these aspects , the present study aimed to identify the inputs and equipment acquired at auctions, likely to cause pain at work; describe the mechanisms used by this subject, and/or creative defensively, as to the possible existence of the suffering related products acquired at auctions and analyze the relationship between labor needs of workers Food and Nutrition Unit and the inputs and equipment procured, implying the psychodynamics of work in order to minimize their possible suffering. Exploratory qualitative study approach, descriptive, which followed from methodological assumptions of a case study, having forty workers as subjects in a university restaurant, Niterói - RJ. Data collection occurred by direct non-participative observation with records in a field diary and photographic and individual semi-structured interviews with questions about working conditions. For data analysis we used the ALCESTE software, which is a computerized technique and also a methodology of lexical content analysis, based on co-occurrences. Data were triangulated and compared with concepts of suffering in the work of Christophe Dejours. The results of this survey respondents were 28 males and 12 females, age ranged between 46 and 55 years, 13 civil servants and 27 contractors, admitted more than 36 months in the unit, with workday of 8 hours/day during the morning, mostly developed in the pre - prepare vegetables and meal distribution sectors. The observation it was found that workers elaborate defensive strategies to minimize labor pain. The analysis of the corpus ALCESTE divided into seven classes, these classes emerged four categories, namely: Perception worker about using uniform, cap and shoes and worker participation in opine on purchase of their tools; Worker's perception about the use of Personal Protective Equipment; Needs and labor difficulties and defensive/creative workers and Strategies - labor difficulties and occupational diseases of workers from the Food and Nutrition Unit. The categories shown discussing working conditions, disturbances/sufferings of workers, their health problems, in addition to conducting defensive/creative strategies to extricate himself from suffering. Labor occurring suffering of workers in the unit researched and it is concluded that this situation leads to the elaboration, by workers of defensive strategies to withstand the harsh conditions of work and that many of their needs for the exercise of their functions may be met the bidding process. This study may contribute to a favorable working condition and health of workers and stimulate the development of future research regarding bidding and work environment.